TINJAUAN TEORITIS PEMBANGUNAN PEDESAAN YANG BERKELANJUTAN: PENGENTASAN KEMISKINAN DAN PERBAIKAN KUALITAS LINGKUNGAN - Sudantoko, H. Djoko; Mariyono, Joko (Universitas Negeri Semarang, 2010)
Rural poverty is major issue faced by developing agrarian countries. It is likely that problem of rural poverty is accompanied by environmental degradation in rural areas. This is because of unique relationship between rural poverty and environmental degradation. This paper tries to raise the problem of poverty and the environment in rural areas. Some cases of poverty level and environmental problem in Asian countries are used to describe the linkage between them. The role of agriculture in rural development is explored. It is for showing that agriculture leads to depletion of rural resources and degradation of rural environment. Last, a solution is proposed that built on theoretical frame work based on microeconomic theory. It is likely that rural development can be conducted with simultaneous actions of poverty alleviation and environmental improvement. One important key to realize this concept is that rural residents need to pay attention on the environment.